The Effectiveness of Garlic Extract on Blood Pressure Reduction in Pregnant Women with Hypertension - Ningsih, Fitriani; Lestari, Rizki Muji; Astika, Vina; Tambunan, Lensi Natalia (International Journal of Clinical Inventions and Medical Sciences (IJCIMS), 2023)
Pregnancy is something that every married couple always looks forward to, but over time not all pregnancies go smoothly. Hypertension in pregnancy is one of the complications that often occur in pregnant women. Hypertension in pregnancy is common and is the leading cause of maternal death, as well as having other serious effects during childbirth. Hypertension in pregnancy occurs in 5% of all pregnancies. Garlic is one type of natural wealth that can lower blood pressure because garlic has active compounds that are known to affect the availability of ions for smooth muscle contraction of blood vessels. This study uses the PICOT format which helps to summarize research questions exploring the therapeutic effect of garlic on hypertension in pregnant women. From the results of an analysis of several previous studies, hypertension can be controlled by regularly taking antihypertensive drugs. In addition to drugs, garlic which is a proven herbal ingredient can be used as an adjuvant to control high blood pressure in hypertensive patients.